2000
DOI: 10.1074/jbc.m008443200
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit Interactions in Plasmodium falciparumThioredoxin Reductase

Abstract: The thioredoxin redox system is composed of the NADPH-dependent homodimeric flavoprotein thioredoxin reductase (TrxR) and the 12-kDa protein thioredoxin. It is responsible for the reduction of disulfide bridges in proteins such as ribonucleotide reductase and several transcription factors. Furthermore, thioredoxin is involved in the detoxification of hydrogen peroxide and protects the cell against oxidative damage. There exist two classes of TrxRs: the high M r and the low M r proteins. The well characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
2
23
0
1
Order By: Relevance
“…The authors (15) suggested that the mobile selenenylsulfide containing a C-terminal tail not only serves as a third redox active group, but it also blocks oxidized glutathione from binding to the enzyme. In addition, the structure confirmed the obligatory ''head-to-tail'' arrangement of high-M r TrxR, with the redox-active C-terminal tail of one subunit interacting with the active site of the opposing subunit (36,37). Unfortunately, the observed conformation of the C-terminal tail precluded direct interaction with the active-site disulfide͞dithiol group, suggesting an additional catalytically competent structural arrangement must exist.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The authors (15) suggested that the mobile selenenylsulfide containing a C-terminal tail not only serves as a third redox active group, but it also blocks oxidized glutathione from binding to the enzyme. In addition, the structure confirmed the obligatory ''head-to-tail'' arrangement of high-M r TrxR, with the redox-active C-terminal tail of one subunit interacting with the active site of the opposing subunit (36,37). Unfortunately, the observed conformation of the C-terminal tail precluded direct interaction with the active-site disulfide͞dithiol group, suggesting an additional catalytically competent structural arrangement must exist.…”
mentioning
confidence: 64%
“…The precise mechanism of selenenylsulfide͞disulfide exchange has not yet been determined for mammalian TrxRs, but studies of D. melanogaster (DmTrxR1) (26,48,49) and P. falciparum (27,37,50) high-M r TrxRs provide considerable insight. DmTrxR1 exhibits significant sequence homology to mammalian TrxRs but is not a selenoprotein (26,48).…”
Section: Figmentioning
confidence: 99%
“…A key intermediate in catalysis is a charge transfer complex (the thiolate of Cys93 is the donor and flavin is the acceptor) characterized by a long-wavelength absorbance around 540 nm. [183,184] A high-throughput-screening program with 350 000 compounds of the Pfizer library yielded about 30 compounds that inhibit thioredoxin reductase. The bewildering chemical diversity among these hits was resolved by Davioud-Charvet et al, who noted that most of them were Mannich bases.…”
Section: Thioredoxin Reductase As a Validated Drug Targetmentioning
confidence: 99%
“…The gene was identified in the genome of P. falciparum, cloned, and expressed as a recombinant functional flavoenzyme. [152,[182][183][184] Subsequently, Müller and co-workers used gene-ablation and gene-substitution techniques to show that thioredoxin reductase is an essential enzyme for the blood stages of P. falciparum. [153,154] These studies validated thioredoxin reductase as a drug target.…”
Section: Thioredoxin Reductase As a Validated Drug Targetmentioning
confidence: 99%
“…These homodimeric proteins contain three redox-active centers that are in redox communication: a tightly bound FAD, a pair of redox-active cysteines on one of the subunits that we will refer to as the N-terminal pair (Cys-88 and Cys-93 in Scheme 1, for PfTrxR), and a pair of redox-active cysteines or a cysteine-selenocysteine pair that we will refer to as the C-terminal pair (Cys-535Ј and Cys-540Ј, for PfTrxR) located on the second subunit (15,22,23,24). The reductive and oxidative half-reactions of Drosophila melanogaster TrxR (DmTrxR) have been examined in some detail to obtain a better understanding of the underlying catalytic mechanism of high-M r TrxRs.…”
mentioning
confidence: 99%